Unworking choreography the notice of the work in dance - Pouillaude, Frédéric 1978- (Oxford studies in dance theory, 2017)
There is no archive or museum of human movement where choreographies can be collected and conserved in pristine form. The central consequence of this is the incapacity of philosophy and aesthetics to think of dance as a positive and empirical art. In the eyes of philosophers, dance refers to a space other than art, considered both more frivolous and more fundamental than the artwork without ever quite attaining the status of a work. This book develops this idea and postulates a désoeuvrement (unworking) as evidenced by a conspicuous absence of references to actual choreographic works within philosophical accounts of dance; the late development and partial dominance of the notion of the work in dance in contrast to other art forms such as painting, music, and theatre; the difficulties in identifying dance works (and developing a philosophical theory of dance identity) given a lack of scores and an apparent resistance within the art form to the possibility of notation; and the questioning of "ends" of dance in contemporary practice and the relativization of the very idea that dance artistic or choreographic processes aim at work production.